Why is Pseudosphromenus cupanus (Teleostei: Osphronemidae) reported from Bangladesh, Indonesia, Malaysia, Myanmar, and Pakistan? - Kullander, Sven O.; Rahman, Md. Mizanur; Norén, Michael; Mollah, Abdur Rob (Zootaxa, 2015)
The native distribution of the small labyrinth fish species Pseudosphromenus cupanus includes southern India and Sri Lanka. According to literature it has a range including also Pakistan, Bangladesh, Myanmar, Malaysia, and Indonesia (Sumatra) but there are no voucher specimens or reliable observations from those areas. The distribution record of P. cupanus was inflated partly by including P. dayi as a synonym. Pseudosphronemus dayi is native to the Western Ghats in India, but the origin of the aquarium importation in 1907 was reported as both Cochin (=Kochi) and Malacca (=Malaysia), the latter locality obviously in error. The basis for the Sumatra record is an obviously mislabeled sample of P. dayi from Pulau Weh close to Sumatra. The basis for reporting the species from Pakistan, Myanmar or Bangladesh could not be located. Misidentified museum specimens from Myanmar and Pakistan identified as P. cupanus were never published on. Pseudosphromenus cupanus has been considered recently to be extinct in Bangladesh, but in fact it never occurred there.